2020
DOI: 10.1007/jhep04(2020)068
|View full text |Cite
|
Sign up to set email alerts
|

Poisson-Lie plurals of Bianchi cosmologies and Generalized Supergravity Equations

Abstract: Poisson-Lie T-duality and plurality are important solution generating techniques in string theory and (generalized) supergravity. Since duality/plurality does not preserve conformal invariance, the usual beta function equations are replaced by Generalized Supergravity Equations containing vector J . In this paper we apply Poisson-Lie Tplurality on Bianchi cosmologies. We present a formula for the vector J as well as transformation rule for dilaton, and show that plural backgrounds together with this dilaton an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 51 publications
0
21
0
Order By: Relevance
“…Matrices C relating Manin triples g g and g ḡ are not unique and different choices may lead to backgrounds with different curvature or torsion properties [47]. However, in [37,38] we have shown that many parameters appearing in general C are irrelevant as the resulting backgrounds differ only by a coordinate or gauge transformation. In such case we choose a representative of the class of C matrices leading to such "equivalent" backgrounds.…”
Section: Poisson-lie T-duality/pluralitymentioning
confidence: 89%
See 4 more Smart Citations
“…Matrices C relating Manin triples g g and g ḡ are not unique and different choices may lead to backgrounds with different curvature or torsion properties [47]. However, in [37,38] we have shown that many parameters appearing in general C are irrelevant as the resulting backgrounds differ only by a coordinate or gauge transformation. In such case we choose a representative of the class of C matrices leading to such "equivalent" backgrounds.…”
Section: Poisson-lie T-duality/pluralitymentioning
confidence: 89%
“…As this has been done in many preceeding papers, e.g. [38], we shall not go into details and restrict to a summary of necessary formulas.…”
Section: Poisson-lie T-duality/pluralitymentioning
confidence: 99%
See 3 more Smart Citations